Body weight gain during adulthood and uterine myomas: Pró-Saúde Study - Karine de Lima Sírio Boclin; Fernanda Pelegrini Torres; Eduardo Faerstein (Universidade de São Paulo, 2015)
This study intended to investigate whether body weight gain during adulthood is associated with uterine myomas. 1,560 subjects were evaluated in a Pró-Saúde Study. Weight gain was evaluated in a continuous fashion and also in quintiles. Odds ratios and 95% confidence intervals were estimated through logistic regression models that were adjusted for education levels, color/race, body mass indices at age 20, age of menarche, parity, use of oral contraceptive methods, smoking, health insurance, and the Papanicolaou tests. No relevant differences were observed regarding the presence of uterine myomas among weight gain quintiles in that studied population.